2016
DOI: 10.1093/brain/aww074
|View full text |Cite
|
Sign up to set email alerts
|

A novel inhibitor of p75-neurotrophin receptor improves functional outcomes in two models of traumatic brain injury

Abstract: The p75 neurotrophin receptor (p75NTR) is a member of the TNF-receptor superfamily. Delbary-Gossart, Lee et al. describe the neuroprotective effects of a novel piperizine derivative that blocks p75NTR. In two rodent models of traumatic brain injury, EVT901 protects neurons and glia, reduces inflammation and seizure susceptibility, and improves neurological outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 45 publications
1
32
0
Order By: Relevance
“…However, this study only tested the effects of the p75 NTR antagonist on other members of the TNF receptor family with cysteine‐rich domains. Thus, they did not exclude interactions of this antagonist with other extracellular receptors which may be an explanation for the altered cell recruitment and activation (Delbary‐Gossart et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, this study only tested the effects of the p75 NTR antagonist on other members of the TNF receptor family with cysteine‐rich domains. Thus, they did not exclude interactions of this antagonist with other extracellular receptors which may be an explanation for the altered cell recruitment and activation (Delbary‐Gossart et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…There have been many reports concerning the physiological and pathological changes after brain injury (Kraus et al, 2007; Roth et al, 2014; Kondo et al, 2015; Delbary-Gossart et al, 2016), and the proliferation and migration of autologous NSCs is a focus of study (Hu et al, 2014; Wang et al, 2016). It has been reported that modeling strokes and TBI in animals has allowed the identification of a unique response in the sub ventricular zone (SVZ), where endogenous neural stem/progenitor cells (NSPCs) undergo transient expansion and begin to migrate to sites of tissue damage (Chen et al, 2003; Thored et al, 2006, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…p75 antagonist that is, EVT 901 was administered daily at an oral dose of 1 mg/kg for a period of 7 days (Delbary‐Gossart et al . ). A corresponding volume of vehicle was administered orally to the placebo animals respectively.…”
Section: Methodsmentioning
confidence: 97%
“…Vitamin E a potent antioxidant was administered daily at an oral dose of 100 mg/kg body weight for the stipulated duration of drug administration (Hong et al 2004). p75 antagonist that is, EVT 901 was administered daily at an oral dose of 1 mg/kg for a period of 7 days (Delbary-Gossart et al 2016). A corresponding volume of vehicle was administered orally to the placebo animals respectively.…”
Section: Animalsmentioning
confidence: 99%